1999
DOI: 10.1021/es990012o
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Weathering, Mobility, and Land Use on Chlordane Residues in Soil

Abstract: The use of technical chlordane, a mixture of 147 separate components, and chlordane-containing products has been illegal in the United States since 1988. Technical chlordane is a member of the persistent organic pollutants (POPs), all of which exhibit remarkably long half-lives in the environment. Due to its persistence, its former use at extremely high application rates, and its toxicity, technical chlordane in soil may be present at levels of concern to public health. Concentrations at a site for which the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 21 publications
4
58
1
Order By: Relevance
“…This wide variation in contamination for both POPs was expected; however, for a given mound, variability among the triplicate soil extractions was less than 5% for chlordane and less than 10% for DDX. These levels of chlordane are in agreement with previous findings (Mattina et al 1999 and the DDX concentrations are indicative of historical contamination with DDT (White 2001;White et al 2007). For chlordane, the component ratios (CR) for TN, TC, and CC were 0.21 (±0.02), 0.32 (±0.02), and 0.46 (±0.02), respectively.…”
Section: Soil Contaminant Concentrationsupporting
confidence: 91%
See 2 more Smart Citations
“…This wide variation in contamination for both POPs was expected; however, for a given mound, variability among the triplicate soil extractions was less than 5% for chlordane and less than 10% for DDX. These levels of chlordane are in agreement with previous findings (Mattina et al 1999 and the DDX concentrations are indicative of historical contamination with DDT (White 2001;White et al 2007). For chlordane, the component ratios (CR) for TN, TC, and CC were 0.21 (±0.02), 0.32 (±0.02), and 0.46 (±0.02), respectively.…”
Section: Soil Contaminant Concentrationsupporting
confidence: 91%
“…The plot (approximately 12m × 21m) was treated with technical chlordane in the 1960s and was subsequently under turf until 1998, when the area was turned over for periodic experimentation. Chlordane residues ranging from 1-18 μg/g have been reported in this soil (6.5% organic matter) (Mattina et al 1999;Eitzer et al 2001). Anecdotal study of this site has also confirmed the presence of p,p -DDT, as well as the metabolites p,p -DDD and p,p -DDE, at concentrations of 50-300 ng/g.…”
Section: Field Sitesupporting
confidence: 59%
See 1 more Smart Citation
“…Sequestration or irreversible adsorption of POPs in the soil matrix over time (Hawthorne and Miller 2003) was also assumed to reduce their bioavailability to soil microbes, fauna such as earthworms (Morrison et al 2000) and, by extension, to flora. Consequently, half-lives of the chemicals in soils range from years (Handbook of Environmental Degradation Rate 1991), to decades (Mattina et al 1999) and even centuries (Kurt-Karakus et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Organochlorine pesticides such as DDT, chlordane, mirex, heptachlor, hexachlorobenzene, toxaphene, and the drins categorized as POPs were banned for use on crops in most developed countries by 1990 3) ; however, because of their long persistence, these compounds are still found in soils. [4][5][6][7] The halflives of dieldrin and endrin in soils are relatively long (5-12 years). 8) Therefore, the risk of drin residues being present in crops cultivated in polluted soils might continue for years or decades.…”
Section: Introductionmentioning
confidence: 99%